If it's not what You are looking for type in the equation solver your own equation and let us solve it.
+3=4(M+9)
We move all terms to the left:
+3-(4(M+9))=0
We calculate terms in parentheses: -(4(M+9)), so:We get rid of parentheses
4(M+9)
We multiply parentheses
4M+36
Back to the equation:
-(4M+36)
-4M-36+3=0
We add all the numbers together, and all the variables
-4M-33=0
We move all terms containing M to the left, all other terms to the right
-4M=33
M=33/-4
M=-8+1/4
| -3(2y+3)=9y-1 | | 2x/4=5x+1/11 | | n-7/2=-8 | | 8x+1=2x+31 | | 2xx11=0 | | 26+-16=-2y | | -41=2/5(45n+60+n) | | 3(m+1)=4(3m+6) | | 6.3g+5=4.3g+13 | | 8.5-2.5=2x+8-8 | | 26+-16=-12y | | h/3=−2 | | T=9y | | 0.5y-4=20 | | 17=3p-4 | | 5/m+4=7 | | 700+15c=1000 | | -1/4(24x-8)+9=8x+3 | | 2m+3=3(m+3) | | 25=4x+-19 | | 9/x^2+x=10 | | 9x+7=5x-4 | | x=√70 | | –2f=–2−2f | | 120+2(4x-4)=180 | | (x+2500-67525)*0.2999999999+x=70130.55 | | 10.6+15x=205.8 | | 3y+18/4=8 | | n/2-10=-18 | | -a+3a-8=9a+7 | | 8p^2+7p-12=0 | | 3,105=20(p+45) |